Low‐Temperature Dependence of the EPR Spectra of Gd0.5RE0.5Ba2Cu3O7−δ Compounds in the Tetragonal Phase - Guskos, N.; V. Likodimos; Londos, C.A.; Windsch, W.; Metz, H.; Koufoudakis, A.; Mitros, C.; Gamari‐Seale, H.; Niarchos, D. (physica status solidi (b), 1992)
The EPR spectra of perovskite ceramics of Gd0.5RE0.5Ba2Cu3O7−δ type (RE  La, Pr, Nd, Sm, Eu, Dy, Ho, Y, Er, Tm, Yb, and Lu) in tetragonal (non‐HTC) phase are investigated as a function of temperature in the range 40 to 3 K. A signal arising from the isotropic exchange interaction of coupled pairs of Cu2+ ions is detected. The intensity of this signal is strongly dependent on the RE ions and its g‐factor varies with temperature. Magnetic measurements show the existence of ferromagnetic anomalies at these low temperature. In the orthorhombic phase, these materials exhibit a superconducting phase transition in the range of 85 to 95 K, apart from the samples with La ions where a TC ≈ 69 K is found and the samples with Prions where a superconducting state can not be observed. Copyright © 1992 WILEY‐VCH Verlag GmbH & Co. KGaA
cited By 6